Bond-slip law and short tie behavior without main cracks. Issue 14 (18th July 2018) - Mezhoud, Djillali; Bouafia, Youcef; Saad, Mohammed; Saliba, Jacqueline
Abstract: The aim of this paper is to study the reinforced concrete short tie-rods behavior using the adhesion-slip curve shape between steel and concrete adopted by the European Concrete Committee. We are interested here in short tie-rods without main cracks for which we calculate and measure the maximum mobilization state of steel-concrete adhesion, and beyond the decrease mode of this bond. For this, tests of short tie-rods, with different high adhesion rebar diameters have been carried out. To characterize the first phase of the adhesion-slip behavior law (τ−g), pull out tests have been carried out with the same concrete, the same reinforcement and the same cross-section such as the tie-rod tests, with a proposed method to estimate the adhesion peak and the corresponding slip. For this adhesion peak value, slightly underestimated by the conventional curve of the European Concrete Committee, a new expression is suggested. A numerical model with theoretical relations of the behavior of such tie-rods is proposed. The comparison of this model with the obtained test curves of the short tie-rods shows a suitable approach. Also, we deduce that the steel (coated with concrete) fictitious module slope is even higher than the percentage of reinforcement is low. These results may help to understand the tie-rods behavior generally, in the phase of cracks stabilization, during which the tie-rod is composed of short tie-rods without main cracks.